Makna dan Relevansi Piagam Madinah dalam Konteks Persatuan Umat, Kebebasan Beragama Konstitusi Negara Modern di Indonesia - Sofyan Wegi Alfariki (Bulletin of Community Engagement, 2024)
The Medina Charter is an important document that emphasizes the principles of unity of the people, and inter-religious harmony in a broad scope including state administration. In the context of Indonesia's pluralistic society, the Medina Charter offers fundamental values that are relevant to building tolerance and mutual respect among various religious groups. This research aims to analyze the Meaning and Relevance of the Medina Charter in the Context of People's Unity and, Freedom of Religion Constitution in Indonesia By using qualitative methods and literature studies, this research found that although Indonesia guarantees freedom of religion through the 1945 Constitution, challenges of intolerance and conflicts between religious communities still exist. Therefore, applying the principles contained in the Medina Charter is essential to create a harmonious and peaceful religious life. The conclusion of this study emphasizes the need for joint efforts from all elements of society to maintain social harmony and stability, to achieve the common goal of creating peace and prosperity amid existing diversity.